MENINGKATKAN KEMAMPUAN MORAL ANAK MELALUI KISAH-KISAH NABI - Amah Suhamah, Dedi Aryadi, Yusdiana (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
This research is aimed at (1) To find out how the application of prophetic stories in improving the moral ability of children of group B in PAUD Aisyiyah Bustanul Athfal Linduk Kecamatan Pontang. (2) To know whether there was an improvement in the moral abilities of the children of Group B in PUD Aishiah Bastanul Athpal Linduk District Pontang after being given action of creativity through the story of the Prophet. Guide I:Dr Dedi Aryadi, M.Pd. Guide II: Yusdiana, M.pd, University of Buddhist Faithfulness (USB) Rangkasbitung 2024. The research method used in this study is the Class Action Research (PTK) method which consists of two cycles and each cycle has three meetings. Subject of this research, the age of 5-6 years in PAUD Aisyiyah Bustanul Athfal Prefecture of Pontang District of Serang. Guides. Research data collection techniques, that is, through observation, and documentation. The results of the research can be concluded that there has been an improvement in the moral knowledge of the children of PAUD Aisyiyah Bustanul Athfal Prefecture of Pontang district of Serang following the story of the Prophet, that is, cycle I by 73.81 % to 80,06 % in the cycle II. Learning to improve the moral development of the child in PAUD Bustanonul Aisyiah Athfal prefecture and Pontang District of the Serang through the tale of the prophet has been well implemented.